Wild lands and the southern sun: claims to north Africa during the thirteenth-century crusades. Issue 3 (27th May 2021) - Cassidy-Welch, Megan
ABSTRACT: Thirteenth-century crusading activity in north Africa reflected many connections between conflict, place and claims to territorial ownership. Crusading encounters with the Almohads and Marinids, Zirids and Hafsids, the Ayyubids and Mamluks, were also encounters with the landscapes and histories of a vast region already part of the biblical and Christian pasts to which crusaders themselves were sometimes imaginatively attached. This paper will consider why and how north Africa (or parts thereof) came to be constructed as holy or sacred territory during the thirteenth-century crusades; and the links between biblical and Christian history, crusading history, and place and space, to trace the construction and language of patrimony and ownership in the landscapes of medieval north Africa.